The characterisation of genetic diversity of a collection of perennial ryegrass (Lolium perenne L.) - McGrath, Sarah Katherine (Trinity College (Dublin, Ireland). Department of Botany, 2008)
Perennial ryegrass (Lolium perenne L.) is a member of the Poaceae family, is native to Europe, the Near East and North Africa and is grown in all the temperate climate areas of the world as a forage and turf grass. Due to its persistence, palatability and nutritive value for ruminants, it is a principal component of pastures, and the most important forage species in Ireland. The primary aim of this thesis was to characterise the level of diversity in a large genetic resource collection of L. perenne germplasm held at Teagasc, Oak Park. Molecular markers, both chloroplast and nuclear SSRs, biochemical characters (water soluble carbohydrate, crude protein, and dry matter), and morphological characters (vegetative and flowering) were used to characterise this diversity, as well as population differentiation, and geographic patterns. Levels of diversity in all systems were found to be high in this collection.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin